Grassland changes and the role of elevation: A global perspective - Yuxin Zhang; Juying Sun; Yafeng Lu; Zhou Shu (Global Ecology and Conservation)
Grasslands cover approximately 40 % of the Earth's land area and provide essential ecosystem services, such as carbon sequestration and biodiversity support. However, global climate change and human activities have significantly altered grassland dynamics, manifesting as ''greening'' and ''browning'' trends in different regions. This study utilized NDVI data, climate data, digital elevation models (DEM), and land-use data from 1981 to 2015, combined with Ordinary Least Squares (OLS) regression, the Mann-Kendall test, residual analysis, and partial correlation analysis, to systematically explore the spatial distribution and driving mechanisms of grassland changes across the 0–5800 m elevation range. Results indicate that the impact of human activities leading to significant grassland greening is primarily concentrated within the 0–1200 m elevation range, while significant browning is predominantly observed at elevations between 0–600 m. The influence of climate change on grassland dynamics spans the entire 0–5800 m elevation range, with particularly pronounced effects between 0–600 m and 1000–1200 m. Temperature was identified as the key climatic factor driving both significant greening and browning of grasslands globally.